MISKOMUNIKASI DAN RUBUHNYA SENDI HARMONI ANTAR KRISTEN-ISLAM DALAM PEMBANGUNAN MASJID AL-MUNAWAR NAHORNOP MARSADA, KABUPATEN TAPANULI UTARA - M. Yusuf Asry (Research and Development Center for Guidance for Religious Societies and Religious Services, the Research and Development and Education and Training Agency of the Ministry of Religious Affairs of the Republic of Indonesia (MORA), 2014)
The Al-Munawar Mosque Sarulla, established in 1941, was in many ways no longer viable as a district mosque. In 1998,the mosque was ordered to be moved, a move that would happen in 2010 to a waqf land on Lintas Sumatra street in Nahornop Marsada village, located in Pahae Jae district, North Tapanuli regency in the province of North Sumatra. While construction of the mosque’s foundation began on 1 February 2013, the project was soon stalled—challenged by the area’s Christian majority through the Community Alliance for Peace in Nahornop Marsada (AMNPK). Why was the mosque rejected? How was the conflict consequently resolved? This study reveals that the Al-Muawar Mosque Sarulla was moved due to legitimate needs, yet was still rejected by the AMNPK. The excuse given were technical, with the organization questioning its appropriateness and feasibility. However, the root of the problem was the inability of the Christian community to coexist with a growing Muslim population. Efforts to resolve the conflict was made by involved parties, the population, and the regency and national governments. The head of the North Tapanuli Regency supported the construction of the mosque, after the Easter and Christmas celebrations in 2012. This support was given after the Muspida and Muspika coordination meeting. Nevertheless, the local government has continued to be unable to resolve the conflict. This article recommends that the resolution of this problem requires that the Chief of Police implement the regent’s orders immediately and that the Office of Religious Affairs and the Local Government should help get the permit for the building of the mosque issued.